Exploring the Potential of Applying Intelligent Buildings (IBs) Features to Enhance Office Buildings' Performance in Yemen - Al-awag , Eman Ali; Wahab, Izudinshah Abd; Al-waraki, Fadl Mohammed; Abass, Fatma (Engineering Research: Perspectives on Recent Advances Vol. 4, 2025)
The evaluation of the IB concept was based on the requirements and definitions of many institutes and countries that consider building intelligence, such as the Intelligent Building Institute (IBI), the European Intelligent Building Group (EIBG), and the Asian Institute of Intelligent Buildings (AIIB). The emergence of Intelligent Buildings (IBs) in the early 1980s marked a qualitative leap in the architecture field. These buildings represent the pinnacle of scientific and technical progress humanity has reached in architecture. IB has an integrated intelligent system that can recognize, make decisions, and respond to variables on its own, in addition to achieving sustainability. With these new concepts in the architecture field, in Yemen, buildings are still traditional in their performance, where individual systems are used. Therefore, this paper aims to investigate the possibility of applying the characteristics of IBs to Yemeni buildings, especially office buildings, to enhance these buildings' performance in order to improve the employees' productivity. To achieve this aim, the study reviewed the characteristics of IBs and the reality of architecture and informatics in Yemen. The Central Organization for Control and Accounting (COCA) case study building was analyzed to represent the contemporary office buildings in Yemen by reviewing its architectural plans, field visits, and interviewing the information technology (IT) management specialist. The study revealed that office buildings in Yemen are suitable for applying the characteristics of IBs, such as intelligent systems (automated lighting, security systems, etc.). These applications can help enhance employee productivity and office building performance in terms of energy efficiency, lowering operational costs, contributing to environmental sustainability, etc. However, the study has limitations, including its focus on a single case study, potential data limitations, and the influence of Yemen's current political and economic context. The case study needs improvements for the building's digital infrastructure, and the information and communication technology (ICT) in Yemen must be updated. Many studies are needed to cover the different aspects of IBs, such as envelopes, materials, etc., in addition to understanding the challenges in applying the IBs' characteristics, the opportunities they provide in improving the buildings' performance in Yemen, and the importance of applying the IBs' characteristics for users (occupants, employees, patients, people with special needs, etc.).